Carvedilol Inhibits Angiotensin II-Induced Proliferation and Contraction in Hepatic Stellate Cells through the RhoA/Rho-Kinase Pathway. (7th November 2019) - Wu, Ying; Li, Zhen; Wang, Sining; Xiu, Aiyuan; Zhang, Chunqing
Abstract : Aim . Carvedilol is a nonselective beta-blocker used to reduce portal hypertension. This study investigated the effects and potential mechanisms of carvedilol in angiotensin II- (Ang II-) induced hepatic stellate cell (HSC) proliferation and contraction. Methods . The effect of carvedilol on HSC proliferation was measured by Cell Counting Kit-8 (CCK-8). Cell cycle progression and apoptosis in HSCs were determined by flow cytometry. A collagen gel assay was used to confirm HSC contraction. The extent of liver fibrosis in mice was evaluated by hematoxylin-eosin (H&E) and Sirius Red staining. Western blot analyses were performed to detect the expression of collagen I, collagen III, α -smooth muscle actin ( α -SMA), Ang II type I receptor (AT1R), RhoA, Rho-kinase 2 (ROCK2), and others. Results . The results showed that carvedilol inhibited HSC proliferation and arrested the cell cycle at the G0/G1 phase in a dose-dependent manner. Carvedilol also modulated Bcl-2 family proteins and increased apoptosis in Ang II-treated HSCs. Furthermore, carvedilol inhibited HSC contraction induced by Ang II, an effect that was associated with AT1R-mediated RhoA/ROCK2 pathway interference. In addition, carvedilol reduced α -SMA expression and collagen deposition and attenuated liver fibrosis in carbon tetrachloride (CCl4 )-treated mice. The in vivo data further confirmed that carvedilol inhibited the expression of angiotensin-converting enzyme (ACE), AT1R, RhoA, and ROCK2. Conclusions . The results indicated that carvedilol dose-dependently inhibited Ang II-induced HSC proliferation by impeding cell cycle progression, thus alleviating hepatic fibrosis. Furthermore, carvedilol could inhibit Ang II-induced HSC contraction by interfering with the AT1R-mediated RhoA/ROCK2 pathway.